Experimental approaches to study the responses to Al stress in cultivated crops - Alcantara, Berenice Kussumoto de (2014)
This thesis was performed in the scope of International Graduation Program in which Universidade de São Paulo and The Ohio State University are inserted. In the first year of Ph.D. work we aimed to understand the effect of aluminum (Al) in root growth of Eucalyptus spp. and the relationship with biochemical parameters and transcriptional responses since there is little information about these responses for tree species. Aluminum is found naturally in the Earth crust, but under acidic conditions Al3+ ion becomes available and toxic to the plants. United States and Brazil possess large areas with Al toxicity and great area of forests growing under these conditions. In order to perform the transcriptional analysis, Eucalyptus RNA was transported to United States, however, the method of transportation was not efficient to guarantee RNA integrity. Therefore we changed our objectives and we performed new experiments using maize as biological system because this species has economical importance to U.S. and Brazil. Furthermore, substantial area of this crop is growing in soils under these conditions. In these experiments, we aimed to verify if pre-treating maize seeds before germination could be efficient to induce Al-tolerance in Al-sensitive genotypes. This thesis was organized in order to build a story based on the sequences of the experiments. In general, we obtained interesting results for Al-sensitive maize that presented reduction in lignin content and gene expression in shoots, also for Al-tolerant variety that present increase in growth, productivity and improvement of nutritional quality of the kernels.